Use of Social Networking Sites (SNS) by Undergraduates of Federal University Oye Ekiti, Nigeria - M. Bankole, Olubanke; Otunla, Aderonke O. (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2021)
Purpose: The revolution of social networking sites (SNS) is a global phenomenon, and has become an inseparable part of daily activities, especially among university students. This study examined pattern of use of SNS by undergraduates of Federal University Oye-Ekiti (FUOYE), Nigeria. Design/methodology/approach: The study employed descriptive survey research design. Multistage sampling procedure was employed to select sample from the total population. The questionnaire method was used as instrument of data collection. Descriptive statistical tools of frequency count, percentage and mean score were employed for the data analysis. Findings: Findings revealed that 98.3% of respondents used Facebook, 95.1% Whatsapp and 86.1% YouTube. For intensity of use, Whatsapp, Facebook, YouTube and Twitter were the most frequently used SNS. The SNS were used more for non-academic engagements (social interactions and daily activities) than for academic related purposes. The students spent average of 4.8 hours per day on SNS. Identified challenges were lack of efficient internet access and too much time spent using SNS. Originality/value: The paper provides useful empirical insight unique to FUOYE on usage of SNS by undergraduates.